The Protagonists of the Institutional Educative Councils: Tension and Dilemmas of the Participation in the Management of the Public School - Carmen Diaz Bazo; Betty Alfaro Palacios; Lilia Calderón Almerco; Neida Álvarez Laveriano (Universidad Autónoma de Madrid, 2016)
The reforms initiates by several countries of the región include the participation of the educative community as a democratic space in which the diverse actors are actively involved in the school life. In Peru, since 2003, -  as a formal mechanism to promote the democratic management of education- different instances of participation, concerting and monitoring have been created, promoted and ruled by the state and which have constituted an opportunity to generate a democratic dynamic in the schools. Such is the case of the Institutional Educative Council (CONEI), organ conformed by the principal, sub-directors, and the representatives of the professors, students and families of each school. In this article, we present some of the outcomes of the research performed on the CONEI at six public schools of the district of Puente Piedra (Lima). Here we analyze -from the same protagonist of the CONEI protagonists and from the micropolitical perspective- two of the questions that guided the work: How is the participation of the CONEI perceived in the school management? And, Which are the tensions encountered? A norm exists that has facilitated the constitution of these organisms in the public schools of the country; nevertheless, it does not have been accompanied of a real change in the conception of participation and, much less it has been translated in an authentic practice of participation. This, as a result of its complexity and the cultural and micropolitical conditions that play in its development. Even though that the speech valuates the inclusion of teachers, students and parents in the management of the school, we have still found a focal point centered in the figure of the principal, the unappreciation of the participation of parents and students, the distrust in the others, and the resilience and fear to lose power.